2007
DOI: 10.1557/proc-1039-p17-03
|View full text |Cite
|
Sign up to set email alerts
|

Boron Doping of Microcrystalline and Nanocrystalline Diamond Films: Where is the Boron Going?

Abstract: We present data showing how the electrical conductivity and Raman spectra of boron doped 'cauliflower'-type nanocrystalline (c-NCD) CVD diamond films vary as a function of B content. The conductivity is roughly linear as a function of B content between an onset threshold of ~5×10 20 cm -3 up to ~6 ×10 21 cm -3, with the higher concentrations giving near metallic conductivity values. The onset threshold may be due to compensating donors due to the large number of impurities and defects in these films. The posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…At low dose of 1.0x10 15 ions/cm 2 (blue line), the sample shows strong Raman peak characteristic for diamond at wave number of 1328 cm -1 , while broaden profile with large full wave half maximum (FWHM) might be related to oxygen concentration at the interface between CVD diamond film and Silicon substrate which is in agreement with result of the STEM-EDX measurement. On the other hand, in sample A-E3D1 implanted with the same ion dose of 1.0x10 15 ions/cm 2 but higher ion energy (red line), the diamond characteristic peak is still stronger while the graphite peak invisible. This proves that the implanted layer is free from graphitic bonds which is in agreement with the study as reported in [13].…”
Section: Raman Spectroscopysupporting
confidence: 86%
See 4 more Smart Citations
“…At low dose of 1.0x10 15 ions/cm 2 (blue line), the sample shows strong Raman peak characteristic for diamond at wave number of 1328 cm -1 , while broaden profile with large full wave half maximum (FWHM) might be related to oxygen concentration at the interface between CVD diamond film and Silicon substrate which is in agreement with result of the STEM-EDX measurement. On the other hand, in sample A-E3D1 implanted with the same ion dose of 1.0x10 15 ions/cm 2 but higher ion energy (red line), the diamond characteristic peak is still stronger while the graphite peak invisible. This proves that the implanted layer is free from graphitic bonds which is in agreement with the study as reported in [13].…”
Section: Raman Spectroscopysupporting
confidence: 86%
“…The first and second order of Silicon substrate Raman peaks are found at the wave number 500 and 1000 cm -1 as corfirmed by May et al [14]. Asymmetry peak profile at wave number 1120 cm -1 may be related to the Fano lineshape due to quantum mechanical interference induced by boron dopant as reported in [15] and this Fano interference effects were much reduced for the smaller grain sized. As indicated by the peak at wave number lower than 500 cm -1 the intensity of paired boron atoms increased and have tendency of build up at crystalline boundary by increasing of ion energy [16].…”
Section: Raman Spectroscopysupporting
confidence: 64%
See 3 more Smart Citations